Inhibition of Potentially Pathogenic Yeastlike Fungi by Clotrimazole in Combination with 5-Fluorocytosine or Amphotericin B - Beggs, William H. (1976)
Clotrimazole (CTM) has a doubtful future with respect to use in treatment of the systemic mycoses. To assess the potential of CTM in combined drug regimens, antifungal effects of CTM together with 5-fluorocytosine (5-FC) or amphotericin B (AMB) were tested in a synthetic liquid medium against Candida albicans, Candida tropicalis, and Torulopsis glabrata. Viable counts were monitored over a 48-h incubation period. Weak inhibitory concentrations of CTM were tested in combination with levels of 5-FC or AMB that alone produced transient antifungal effects followed by rapid recovery of proliferative capacity. Results were similar for each of the organisms studied. Between 24 and 48 h, when cultures containing 5-FC or AMB alone were in the recovery phase, CTM plus 5-FC and CTM plus AMB continued to markedly suppress cell multiplication. It would appear that weak inhibitory concentrations of CTM can act together with 5-FC or AMB to produce antifungal effects greater than that obtained with either of the latter two drugs alone.